Implementation of Deep Learning Approach through 5E Learning Model - Risca Amani; Rahmahtrisilvia Rahmahtrisilvia; Marlina Marlina; Ahmad Fauzan (LPPM Undiksha, 2026)
This research is motivated by the persistence of surface learning practices in many schools, which tend to emphasize memorization and provide little space for in-depth understanding. This condition hinders the development of 21st-century competencies such as critical thinking, collaboration, and reflection. The purpose of this study is to analyze the implementation of the 5E instructional model as a deep learning framework. This study uses a qualitative approach with a case study design. The research subjects consisted of 4 facilitators, 1 principal, 1 curriculum coordinator, 2 students, and 2 parent representatives. Data were collected through interviews, observations, and document analysis of Unit Plans, Activity Plans, and assessment rubrics. The data were then analyzed using the Miles & Huberman thematic approach. The results show that the facilitators successfully adapted the formal curriculum into a contextual thematic curriculum through the consistent application of the five phases of the 5E model. This approach increased student engagement, built meaningful understanding, and encouraged collaboration and critical reflection. The assessment rubric included authentic, process-based indicators, although knowledge transfer to cross-disciplinary contexts remained limited. Furthermore, parental and community involvement also play a crucial role in building a holistic learning ecosystem. It can be concluded that integrating a deep learning approach with the 5E model is effective in developing 21st-century competencies across the cognitive, affective, and social dimensions. This research emphasizes the importance of contextual curriculum innovation, authentic assessment, and educational ecosystem synergy as sustainable 21st-century learning strategies.